2017
DOI: 10.1128/aac.02034-16
|View full text |Cite
|
Sign up to set email alerts
|

Differential Penicillin-Binding Protein 5 (PBP5) Levels in the Enterococcus faecium Clades with Different Levels of Ampicillin Resistance

Abstract: Ampicillin resistance in Enterococcus faecium is a serious concern worldwide, complicating the treatment of E. faecium infections. Penicillin-binding protein 5 (PBP5) is considered the main ampicillin resistance determinant in E. faecium. The three known E. faecium clades showed sequence variations in the pbp5 gene that are associated with their ampicillin resistance phenotype; however, these changes alone do not explain the array of resistance levels observed among E. faecium clinical strains. We aimed to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
66
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(73 citation statements)
references
References 40 publications
6
66
1
Order By: Relevance
“…On the other hand, since the complete pbp5 gene of these isolates has not been amplified and sequenced, other substitutions present in the N-terminal, non-penicillin binding domains may also contribute to the high level of resistance observed in these isolates. Regarding PBP5 expression, our results are in agreement with the results of the study conducted by Montealegre et al (21) on the expression of different PBP5 variants in the context of the background clade. Their results showed that there was a clear difference in the expression of PBP5 between clades, that is, comparing the PBP5 expression by clade A strains with its expression by clade B strains.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…On the other hand, since the complete pbp5 gene of these isolates has not been amplified and sequenced, other substitutions present in the N-terminal, non-penicillin binding domains may also contribute to the high level of resistance observed in these isolates. Regarding PBP5 expression, our results are in agreement with the results of the study conducted by Montealegre et al (21) on the expression of different PBP5 variants in the context of the background clade. Their results showed that there was a clear difference in the expression of PBP5 between clades, that is, comparing the PBP5 expression by clade A strains with its expression by clade B strains.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, two susceptible isolates (allele E) were the only isolates that showed much lower expression of PBP5 compared to isolates with MIC ≥ 128. Thus, ampicillin MICs were correlated with PBP5 expression, consistent with those of Montealegre et al (21). According to our results, it is possible that pbp5 variants in various isolates confer different PBP5 affinity and as a result, posttranslational modification of PBP5 or different binding to ampicillin may occur (24).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This frequently involves the duplication of a gene and the concomitant overexpression of the encoded protein (Jensen 1976; Ohno 2013; Patrick et al 2007; Näsvall et al 2012; Kacar and Gaucher 2012; Herron and Doebeli 2013; Levin et al 2014; Hughes and Andersson 2015; Montealegre et al 2017; Notebaart et al 2018). …”
Section: Introductionmentioning
confidence: 99%